Effect of a 12-week home-based exercise protocol on muscle mass, liver and spleen stiffness, and quality of life in patients with liver cirrhosis - Kamble, Maitreyi; Devi Thangavelu, Poovishnu (Journal of Neonatal Surgery, 2025)
A condition that is characterized by the formation of fibrosis and nodular patterns on the liver due to chronic injury to the liver caused by conditions such as hepatitis, alcoholic liver disease, NASH, etc., is known as liver cirrhosis. A multidimensional approach is always established by exercise towards the betterment of an individual. With the aim of assessing the effect of structured exercise on liver cirrhosis, this study is performed accordingly. A specific formula was taken into consideration to develop a sample size for the participation. A total enrollment of 40 patients was done in this study, who were randomly divided into 2 groups: one was a control group and the other was an experimental group. A simple exercise program was allotted to the control group, and the experimental group underwent a structured exercise program. Outcome measures, which included bioelectric impedance, ultrasound measures for liver and spleen stiffness, and the CLD questionnaire, were assessed before the program as well as after the program. The results were obtained accordingly. The mean muscle mass in the experimental group increased from 24.21 ± 3.99 kg to 30.79 ± 6.44 kg (p < 0.001) with between group difference of p= 0.002 which is considered statistically significant. The mean liver stiffness of experimental group decreased from 11.0 ± 0.82 kPa to 9.32 ± 0.88 kPa (p < 0.001) with between group difference of p= 0.040 suggesting the comparatively greater effectiveness of structured exercise protocol on the patients. The mean spleen stiffness decreased from 30.79 ± 2.72 kPa to 28.42 ± 3.16 kPa (p < 0.001) with between-group post-intervention comparison of 1.18 kPa, which was although modest statistically but significant clinically. While assessing the quality of life of the participant, a statistically significant improvement in fatigue experienced my patient was seen with p value of <0.0001 whereas, the activity symptoms showed p value of 0.05 which was although modest but clinically significant. Thus, promoting the effectiveness of a structured exercise protocol in the betterment of patients with liver cirrhosis